Adjunctive Efficacy of Superior Hypogastric Plexus Block in Chronic Pelvic Pain: A Comprehensive Review - Vivek Chakole; Shrilekh Mankhair; Priyanka Dev; Jeshnu Tople; Ranjit S Ambad (Journal of Pharmacy and Bioallied Sciences)
Chronic pelvic pain (CPP) is a prevalent and complex condition that affects millions worldwide, predominantly women, and poses significant challenges in both diagnosis and management. Despite a wide array of pharmacological and nonpharmacological treatments, many patients experience persistent pain, reduced quality of life, and limited functional capacity. The superior hypogastric plexus block (SHPB) has emerged as a promising interventional technique for the management of CPP, particularly in cases with predominant visceral pain components. This comprehensive review aims to evaluate the adjunctive efficacy of SHPB in treating CPP, exploring its anatomical basis, mechanisms of action, and clinical outcomes. SHPB targets the superior hypogastric plexus, a crucial relay center for transmitting nociceptive signals from the pelvic organs. By interrupting these pathways, SHPB can relieve pain and improve associated symptoms such as dysmenorrhea, dyspareunia, and dysuria. This review systematically analyzes the existing literature on SHPB, comparing its effectiveness with other interventional techniques and its role as an adjunct to standard therapies. Evidence suggests that SHPB can significantly reduce pain scores and improve the quality of life in selected patients with a relatively low risk of complications.